Coping Strategies and Self-Efficacy in University Students: A Person-Centered Approach - Freire, Carlos; Ferradás, María del Mar; Regueiro, Bibiana; Rodríguez, Susana; Valle, Antonio; Núñez, José Carlos (Frontiers in Psychology, 2020)
In daily academic life, students are exposed to a wide range of potentially stressful situations which could negatively affect their academic achievement and their health. Among the factors that could be weakened by academic stress, attention has been paid to expectations of self-efficacy, which are considered one of the most important determinants for student engagement, persistence, and academic success. From a proactive perspective, research on academic stress has emphasized the importance of coping strategies in preventing harmful consequences. In recent years, there has been a growing interest in discovering the extent to which individuals are able to combine different coping strategies and the adaptive consequences this flexibility entails. However, studies using this person-centered approach are still scarce in the academic context. On that basis, this current study had two objectives: (a) to examine the existence of different profiles of university students based on how they combined different approach coping strategies (positive reappraisal, support seeking, and planning); and (b) to determine the existence of differences in general expectations of self-efficacy between those coping profiles. 1072 university students participated in the study. The coping profiles were determined by Latent Profile Analysis (LPA). The differences in the self-efficacy variable were determined using ANCOVA, with gender, university year, and degree type as covariates. Four approach coping profiles were identified: (a) low generalized use of approach coping strategies; (b) predominance of social approach coping approaches; (c) predominance of cognitive approach coping approaches; (d) high generalized use of approach coping strategies. The profile that showed that a greater combination of the three strategies was related to higher general self-efficacy expectations, and vice versa. These results suggest that encouraging flexibility in coping strategies would help to improve university students’ self-efficacy.